CIP deviations in BRICS countries around the 2008 global financial crisis - Gadish, Adi (2021)
The covered interest rate parity (CIP) has failed to hold among emerging markets long before the 2008 global financial crisis. The reasons for those CIP deviations range from transaction costs and risk premia demanded by market participants to provide liquidity in an illiquid market and carry out transactions with less credit-worthy counterparties, as well as credit risk, low degree of financial integration, and perceived country risk. This paper examines the effect of the 2008 global financial crisis on CIP deviations among the five largest emerging markets, Brazil, Russia, India, China, and South Africa (BRICS). Additionally, the global and local economic policy uncertainty are tested as potential new explanations for CIP deviations. In this research, the BRICS countries’ CIP deviations are tested against the euro in the period of 2004-2019 to represent the periods before and after the 2008 global financial crisis. With the aid of the Vector Autoregression (VAR) model and the Granger causality tests, the relationships between multiple variables are captured and the predictive power of the variables is tested. In order to capture the negative interest rate era in the eurozone, a dummy variable is estimated to test whether the economic policy uncertainty variables should be treated as an endogenous or exogenous variable. This research finds for 80% of the cases that the magnitude of CIP deviations for BRICS countries has increased substantially following the 2008 global financial crisis in comparison to the pre-crisis era, while in only 20% of cases, the 2008 financial crisis appears to have not affected the magnitude of the CIP deviations. Furthermore, The results also find that in 30% of the cases, global EPU causes CIP deviations while in 20% of the cases, country-level EPU causes CIP deviations.